Literature Review of Integrated Management System (IMAS) and Implementation Suggestion in the Defense Industry - Radyawanto , Aris Setyo; Soediantono, Dwi (International Journal of Social and Management Studies, 2022)
The purpose of this article is to explore the benefits of implementing the Integrated Management System (IMAS) in various industries and to provide suggestions for application to the defense industry. The method of writing this article is a literature review, namely reviewing by collecting, understanding, analyzing and then concluding as many as 30 international journal articles on Integrated Management Systems (IMAS) published from 2015 to 2021 regarding the application of the Integrated Management System (IMAS) method in various industrial sectors and the defense industry. . The analysis used is 30 journal article content analysis. The results of the literature review analysis state that the implementation of the Integrated Management System (IMAS) can be effective in the community, can create consistency, focus more on solving problems, align responsibilities and authorities, align goals, can reduce risk and increase profits and can reduce duplication of work. The benefits of the integration include assisting in the implementation of integrated management systems, helping to obtain more business opportunities, Assisting in monitoring, assessing and evaluating the effectiveness of management systems in the form of integration audits, helping to increase the credibility of the organization/company, assisting in updating accredited international standards. such as cost savings, operational benefits, better external image and increased customer satisfaction. so the Integrated Management System (IMAS) is recommended to be applied in the defense industry.